THE EFFECTIVENESS OF USING COMIC STRIPS TOWARD STUDENTS' WRITING ABILITY IN MAKING DESCRIPTIVE TEXT - Zul Aini Rengur; Fatima (Datokarama English Education Journal, 2022)
The aim of this research is to find out the effectiveness of using comic strip toward writing ability in making descriptive text. The research belongs to experimental research. The population of this research is the eighth grade of SMPN 7 Ambon consisting 210 students. The researchers took 60 students as the samples and the samples were divided into control group (VIII 3) consists of 30 students and experimental group (VIII 2) consists of 30 students. The researchers conducted testing to get the data (pre-test and post-test) in control group and experimental group. The researchers used descriptive and inferential analysis to analyze the data. The descriptive analysis shows that the result of experimental group shows that in pre-test, the mean is 37.20, the standard deviation is 22.69, and the highest category belongs to very poor category with 53.3% (16 students). While in the post-test the mean is 60.60, the standard deviation is 27.47, and the highest category belongs to very good category with 30.0% (9 students). Meanwhile, the result of control group shows that in pre-test, the mean is 43.26, the standard deviation is 28.20, and the highest category belongs to very poor category with 40.0% (12 students). While in the post-test, the mean is 48.16, the standard deviation is 19.12, and the highest category belongs to fair category with 50.0% (15 students). It means the hypothesis is accepted. There is a significance difference between the students taught using comic strip in making descriptive and those taught without using comic strip in making descriptive text in the eighth grade of SMPN 7 Ambon.